Worlds of Sound: Indie Games, Proceduralism, and the Aesthetics of Emergence. Issue 2 (December 2015) - D'Errico, Michael
Abstract : In the first decades of the twenty-first century, 'indie' became a widespread descriptor for a gaming culture comprising developers, players, and distributors interested in creating an alternative to what was seen as a glutted, uninspired, and corporatised game market. While the indie movement is often argued to have facilitated a new, 'DIY' mentality in the design and practice of games and interactive media, the aesthetics and technical practices behind the culture share strong affinities to computational forms of art and music throughout the late twentieth century. This essay aligns the aesthetics and creative practices of indie game designers with traditions of 'generative' art and music from the late twentieth century. In doing so, I outline a broader musical turn that has occurred within gaming culture—one in which sound becomes a primary mechanic in the shaping of 'procedural' and generative aesthetics at the heart of various forms of digital art. Ultimately, I provide not only an account of the ways in which sound and musical design have helped to characterise the ludic interests of the indie game movement in the first decades of the twenty-first century, but also a theoretical model adequate to understand the relationship between interactive systems, musical and sonic meaning, and user experience both in games and digital platforms more broadly.